2017
DOI: 10.1159/000477595
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside-IV Protects Against Heat-induced Apoptosis by Inhibiting Excessive Activation of Mitochondrial Ca2+ Uniporter

Abstract: Background: Heat causes airway damage during inhalation injury because of bronchial epithelial cell damage. Accumulating evidence shows that mitochondrial uniporter (MCU) is involved in cell damage. We investigated the MCU activity after heat treatment and assessed whether Astragaloside-IV (AS-IV) suppresses heat-induced apoptosis in bronchial epithelial cells by inhibiting the activation of the mitochondrial Ca2+ uniporter (MCU), mitochondrial depolarisation and reactive oxygen species (ROS) produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Mitochondrial calcium uniporter (MCU) has been identified as a mitochondrial calcium uptake channel; MCU dysfunction, caused by ROS generation, leads to calcium overload and disruption of MMP. Furthermore, hyperthermia has been shown to induce cell apoptosis via MCUmediated mitochondrial calcium overload [49,50]. Our findings suggest that nonivamide enhances hyperthermia-induced ROS generation, and that production of ROS can be decreased by combined treatment with the ROS scavenger NAC (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Mitochondrial calcium uniporter (MCU) has been identified as a mitochondrial calcium uptake channel; MCU dysfunction, caused by ROS generation, leads to calcium overload and disruption of MMP. Furthermore, hyperthermia has been shown to induce cell apoptosis via MCUmediated mitochondrial calcium overload [49,50]. Our findings suggest that nonivamide enhances hyperthermia-induced ROS generation, and that production of ROS can be decreased by combined treatment with the ROS scavenger NAC (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Leukocytes were isolated using gradient centrifugation with Percoll [19, 20]. To isolate MPs, 250 µL platelet-free plasma was thawed on ice for 60 min and then centrifuged for 45 min at 20, 000 × g , as in a previous report [28]. …”
Section: Methodsmentioning
confidence: 99%
“…A recalcification time assay was used to assess PCA in a KC4A coagulometer [28]. All clotting assays were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Astragaloside IV (AS‐IV; chemical structure shown in Figure ) is a monomeric compound purified from A. membranaceus . In addition, in vivo and in vitro experiments have shown that AS‐IV has anti‐inflammatory, antiapoptotic, and antioxidative effects (Dong et al, ). Moreover, it has been observed that AS‐IV can protect against cardiomyocyte death by modulating mitochondrial membrane permeability (Guan, Yang, Liu, & Yang, ).…”
Section: Introductionmentioning
confidence: 99%